Prémisses de la critique textuelle dans la culture écrite du XVIII-e siècle - Eugen Pavel (Revista de Istorie și Teorie Literară)
Without becoming a current and fully accepted practice, the application of textual criticism in the eighteenth century undergoes several attempts to impose itself in the practice of publishing and printing. There are written proofs of the attempts done at the royal court of Nicholas Mavrocordatos, among which the ones made by Transylvanian Hellenist specialist Stephan Bergler to critically edit some medieval manuscripts, followed by the hard work of some typographic correctors, such as the Greek monk Mitrofan Gregoras, or as the monks Rafail, Anatolie and Lavrentie, from the Hurezi convent, and also Mihalcea Litterati or Cozma Vlahul, who prove their incipient qualities of editors. An animator and mentor of the editing process would also be the Moldavian hierarch Leon Gheuca. The maturity of the textual criticism is reached in this period through the Bible from Blaj, published by Samuel Micu in 1795. The new Biblical version distinguishes itself through the accuracy of editing, the book being endowed with other complementary texts, such as two prefaces, the introductions to the different groups of books and to each book taken apart, as well as abstract of the chapters. To all these we should add the infrapages of glosses on the history of the sources, completed with several versions of traduction, whereby a negative critical apparatus is developed, comparable with the modern structure of a rigorous edition.